Arc of Empire : America's Wars in Asia from the Philippines to Vietnam - Hunt, Michael H.; Levine, Steven I. (Book collections on Project MUSE., 2012)
"Although conventionally treated as separate, America's four wars in Asia were actually phases in a sustained U.S. bid for regional dominance, according to Michael H. Hunt and Steven I. Levine. This effort unfolded as an imperial project in which military power and the imposition of America's political will were crucial. Devoting equal attention to Asian and American perspectives, the authors follow the long arc of conflict across seventy-five years from the Philippines through Japan and Korea to Vietnam, tracing along the way American ambition, ascendance, and ultimate defeat. They show how these wars are etched deeply in eastern Asia's politics and culture"--Publishers description.